Worry and Hope: What College Students Know, Think, Feel, and Do About Climate Change - Krista K. Hiser; Matthew K. Lynch (The University of Alabama, 2021)
"Colleges and universities can only thrive if society and the biosphere are healthy. Any institution that is so shortsighted as to pursue its ends without taking into account the interests of the larger community or ecosystem in which it is enmeshed will not achieve sustainable success. In the end, it will find itself forced, one way or another, to deal with the fact that its future is linked to that of the larger web of social and ecological relations" (Bardaglio & Putman, 2009, p. 174). "You are not mature enough to tell it like it is. Even that burden you leave to us children" (Thunberg, 2018).